Bank balance sheet constraints and bond liquidity - Johannes Breckenfelder; Victoria Ivashina (European Central Bank (ECB), 2021)
We explore the ties between bonds and individual dealers formed through home advantage and the persistence of previous underwriting relationships. Building on these connections, we show that the introduction of the leverage ratio for the European banks had a large impact on exposed bonds' liquidity. Moreover, based on these ties, we show that bond mutual fund panic following the 2020 pandemic outbreak affected substantially more mutual funds with the larger exposures to dealer banks' balance sheet constraints.
Keywords: G12; G18; G21; 330; Bond liquidity; market-making; capital requirements; leverage ratio; mutual funds; COVID-19